Applying the Mental Capacity Act to research with people with learning disabilities. (June 2015) - Jepson, Marcus; Williams, Val; Tarleton, Beth
<x xml:space="preserve">Abstract</x> Accessible Summary People with learning disabilities should be included in research that is about them. There is a law in England and Wales called the Mental Capacity Act that has rules that researchers must follow. This paper shows how one researcher used those rules to ensure people with learning disabilities were able to be involved in a research project. Summary This study describes the experiences of a researcher negotiating consent with people with learning disabilities to become participants in a research study. The study was about how the Mental Capacity Act (MCA) was applied to everyday decision‐making in social care settings. However, before data collection could begin, the researcher had to follow the principles of the MCA and the requirements of ethical research practice. The study reports on the important role of gatekeepers in allowing (or preventing) access to potential participants. However, gatekeepers did not always act in a manner in keeping with the first principle of the MCA. Additionally, the dilemmas for a researcher in assessing participants' capacity to consent to the study are described, as are three approaches followed which supported people to decide for themselves.